PENGARUH VISUALISASI PESAN PERSUASIF KAMPANYE #PAKAISAMPAIHABIS TERHADAP PERUBAHAN PERILAKU FOLLOWERS MENGKONSUMSI PRODUK KECANTIKAN - Yunita; Agustini; Nadia Amalia (Universitas Djuanda Bogor, 2023)
The increase in beauty industry waste due to the trend of using beauty products in Indonesia, unfortunately, is not accompanied by public awareness of the environmental impacts caused. The #PakaiSampaiHabis campaign seeks to raise public awareness of the consumption of beauty products through the spread of persuasive messages in the form of visualization on Instagram @lyfewithless. The study aims to determine the effect of visualization of persuasive messages in the #PakaiSampaiHabis campaign on Instagram @lyfewithless on changes in followers' behavior in consuming beauty products. The research uses descriptive quantitative methods. Primary data was obtained from the results of a questionnaire of 100 Instagram followers @lyfewithless and interviews, while secondary data was obtained through literature studies. The data analysis technique uses Simple Linear Regression, Coefficient of Determination, and F Test. The results showed that message visualization in the #PakaiSampaiHabis campaign played a role of 64.6% in influencing changes in followers' behavior in consuming beauty products. Visualization of persuasive messages in the #PakaiSampaiHabis campaign with sound and music indicators is the main factor that attracts followers' attention in receiving and understanding the campaign. Changes in the behavior of followers consuming beauty products are in the contemplation stage in the form of high awareness to be responsible for the use of beauty products.